2012
DOI: 10.1242/dev.069070
|View full text |Cite
|
Sign up to set email alerts
|

The role of Hes genes in intestinal development, homeostasis and tumor formation

Abstract: SUMMARYNotch signaling regulates intestinal development, homeostasis and tumorigenesis, but its precise downstream mechanism remains largely unknown. Here we found that inactivation of the Notch effectors Hes1, Hes3 and Hes5, but not Hes1 alone, led to reduced cell proliferation, increased secretory cell formation and altered intestinal structures in adult mice. However, in Apc mutation-induced intestinal tumors, inactivation of Hes1 alone was sufficient for reducing tumor cell proliferation and inducing diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 50 publications
8
100
0
Order By: Relevance
“…Our data showing that elevated apoptosis was reversed by Notch1 ICD overexpression in VBN mice demonstrate that marked downregulation of Notch signaling is responsible for increased apoptosis in Brg1-deficient duodenum. This finding is consistent with a previous report showing that Notch inhibition by conditional knockout of Hes1, Hes3 or Hes5 results in increased apoptosis in murine intestinal epithelial cells (Ueo et al, 2012). A previous study shows that apoptotic cells are increased only in crypt lesions in adult Brg1 mutant mice (Holik et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data showing that elevated apoptosis was reversed by Notch1 ICD overexpression in VBN mice demonstrate that marked downregulation of Notch signaling is responsible for increased apoptosis in Brg1-deficient duodenum. This finding is consistent with a previous report showing that Notch inhibition by conditional knockout of Hes1, Hes3 or Hes5 results in increased apoptosis in murine intestinal epithelial cells (Ueo et al, 2012). A previous study shows that apoptotic cells are increased only in crypt lesions in adult Brg1 mutant mice (Holik et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In particular, Notch signaling plays a crucial role in the regulation of progenitor cell proliferation and differentiation (Sancho et al, 2015). Notch activity promotes differentiation into the absorptive-type cell lineage rather than the secretory cell lineage (Fre et al, 2005;Jensen et al, 2000;Milano et al, 2004;Ueo et al, 2012;van Es et al, 2005;VanDussen et al, 2012;Wong et al, 2004;Yang et al, 2001). Complete inhibition of Notch signaling in the murine intestinal epithelium using γ-secretase inhibitors results in significantly elevated differentiation into secretory lineages (Milano et al, 2004;van Es et al, 2005;Wong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous inactivation of Hes1, Hes3 and Hes5 in the small and large intestine leads to an accumulation of secretory cells and to a decrease in proliferation within the crypt compartment (Ueo et al, 2012). Similarly, in vivo studies identified Delta-like 1 and Delta-like 4 as physiological ligands for Notch receptors in this context.…”
Section: Kip2mentioning
confidence: 84%
“…5B): loss of Math1 in the intestine leads to loss of the secretory cell population, whereas gain-of-function causes an accumulation of secretory cells at the expense of the absorptive EC lineage (Yang et al, 2001;VanDussen and Samuelson, 2010). Active Notch signaling in stem/progenitor cells of the intestine favors the absorptive over the secretory cell fate (Ueo et al, 2012), and the accumulation of secretory cells observed in the absence of Notch signaling can be rescued by depletion of Math1. Furthermore, Math1 has also been shown to regulate proliferation in the crypt compartment, as loss of Math1 on a Notch-deficient background re-establishes Hes1 expression, thus restoring proliferation in the crypt compartment (Kim and Shivdasani, 2011).…”
Section: Kip2mentioning
confidence: 99%
“…Hes1 knockout (KO) mice showed an overproduction of secretory cells (Jensen et al, 2000). Importantly, Hes1 inactivation markedly reduces tumor cell proliferation and induces their differentiation into intestinal epithelial cells without affecting the homeostasis of normal intestinal crypts in adenomatous polyposus coli (Apc) mutation-induced intestinal tumors, suggesting that Hes1 is a promising target for intestinal cancer therapy (Ueo et al, 2012).…”
Section: Roles Of Hes Factors In Various Tissuesmentioning
confidence: 99%